VIABILITAS RUMPUT SORGHUM (Sorghum sp.) PADA MEDIA PERSEMAIAN YANG BERBEDA - Saragih, Evi Warintan (Fakultas Peternakan Universitas Papua, 2010)
Viability test are using to find out quality of seed. Viability of Sorghum sp. was tested by using three different media of germination through experimental field. Three different media of germination are sand (100%), composite of sand and soil 50%:50% and 75%:25%. Research variables of this study were germination percentage, daily rate of germination, average daily germination, culmination of germination and germination value. The results showed that there was no significant different between three different media of germination on germination percentage, daily rate germination, average daily germination and germination value. The significant different between three media of germination was only found on culmination germination. Moreover, composite sand and soil (50%:50%) media revealed good performance for Soghum sp germination. It mean this media suitable for germination.